PERAN PEREMPUAN DALAM PENDIDIKAN BUDI PEKERTI - SHOLEH, MUHAMMAD (Yinyang: Jurnal Studi Islam Gender dan Anak, 2017)
Basically Islam gives the equal rights to men and women hence there is no prohibition for a woman to develop herself either as an individual, a mother, a wife or a society member. One of the roles she can take is giving character education to her children. As a mother, a woman is demanded to give affection wisely and to be a good model for her children, especially in developing children’s good personality.